2022
DOI: 10.3390/en15145248
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Renewable Energy Community Designs for District Heating Networks: Case Study of Corticella (Italy)

Abstract: In recent years, a rapid increase in the adoption of renewable energy sources and in the transition from a centralized electricity generation system to an increasingly distributed one has occurred. Within this scenario, in line with the European directives for achieving the objectives in the field of energy transition and climate change, energy communities are seen as potential contributors. The purpose of this work is to analyze the application potential of the energy community concept associated with distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…At the same time, the increasing installation of heat pumps is associated with increased peak loads of electricity [12,14]. Another efficient strategy for decarbonising residential buildings is using heat pumps and photovoltaic (PV) panels [14,15]. The integrated work of air-source heat pumps and grid-connected PV panels as an optimal solution for residential buildings is also pointed out by Stamatellos et al [16][17][18].…”
Section: Finland's Goal: Ending Fossil Fuel Oil Heating In Buildingsmentioning
confidence: 97%
See 1 more Smart Citation
“…At the same time, the increasing installation of heat pumps is associated with increased peak loads of electricity [12,14]. Another efficient strategy for decarbonising residential buildings is using heat pumps and photovoltaic (PV) panels [14,15]. The integrated work of air-source heat pumps and grid-connected PV panels as an optimal solution for residential buildings is also pointed out by Stamatellos et al [16][17][18].…”
Section: Finland's Goal: Ending Fossil Fuel Oil Heating In Buildingsmentioning
confidence: 97%
“…Some studies have shown that replacing existing boilers with heat pumps ensures better urban air quality [13]. At the same time, the increasing installation of heat pumps is associated with increased peak loads of electricity [12,14]. Another efficient strategy for decarbonising residential buildings is using heat pumps and photovoltaic (PV) panels [14,15].…”
Section: Finland's Goal: Ending Fossil Fuel Oil Heating In Buildingsmentioning
confidence: 99%
“…Another limit of the energy community configuration is highlighted in the installation of photovoltaics in cities and, specifically, on condominium rooftops due to both the limited surface available and the shading effect of other attached and nearby buildings [46,47]. Finally, some of the studies stressed the possibility that the more significant effect on energy consumption reduction is connected to the improvement of building energy efficiency [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several case studies have shown promising results in the transition from traditional heating systems to HPs and combining various renewable energy sources, including HPs, solar energy, common storage facilities, and similar synergies. These efforts aim to improve heating efficiency in both individual and district heating (DH) solutions [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%